Routes to cellulosic ethanol - Buckeridge, Marcos Silveira; Goldman, Gustavo Henrique (Springer, 2011)
The quest for renewable energy and sustainability have led to the examinaiton of using biomass as a source of energy. Since large amounts of energy are "hidden" in carbon polymers made by plants, notably carbohydrates, the development of technologies to produce liquid fuels from carbohydrate polymers such as cellulose could significantly increase energy sustainabiligy. This book reviews general aspects of biomass utilization for bioenergy production, as well as strategies using biochemistry, molecular biology, chemistry and physics to disassemble plant cell walls. Recent discoveries of basic science under development in several laboratories are reviewed by experts who have been working intensively with aspects that will have an impact on the development of the technology of production of cellulosic ethanol -- Source other than Library of Congress.